(untitled) (International Journal of Engineering and Computer Science, 2017)
Reliability is defined as the ability of a system or component to perform its required functions under stated conditions for a specified period of time.There are various parameters which improves the reliability of the software.It is necessary to maintain the reliability of the software to keep track of correct information about any company the details of the information includes resource, money, employees, transaction details and many more, Now a days demand on complex systems has increased more rapidly. The size and complexity of computer systems has grown during the past decades in a very impressive manner.Due to the increase in size and complexity of the systems it become difficult to maintain the reliability of the system.Software reliability is closely related to safety engineering and system safety, in that they use common methods for their analysis and may require input from each other. Software reliability focuses on costs of failure caused by various threats, software failure and many more.Various approaches can be used to improve the reliability of the software, however, it is hard to balance development time and budget with software reliability. But the best approach to assure software reliability is to develop a high quality software through all of the stages of software life cycle.